1142. Use of DNA Markers to Assess the Potential for Pathogen Transmission from Physicians' White Coats. (26th November 2018) - Van Aartsen, Daniel; Thakur, Manish; Dousa, Khalid M; Kanwar, Anubhav; Cadnum, Jennifer; Wong, Yilen Karen Ng; Mana, Thriveen; John, Amrita; Alhmidi, Heba; Donskey, Curtis J
Abstract: Background: Physicians' white coats are often contaminated, but seldom cleaned. A "bare below the elbows" dress code policy has been advocated as a strategy to reduce the risk for transmission of healthcare-associated pathogens by white coats. However, transfer of contamination by clothing has not been demonstrated in clinical settings and it is not known if long sleeves are the major source of transfer. Methods: We observed physicians during routine patient encounters and characterized the frequency of direct and indirect contact between white coats and the patient or environmental surfaces. To assess transfer from white coats in clinical settings, we applied one cauliflower mosaic virus DNA marker to the sleeve cuffs and another to the coat pockets of physicians prior to routine patient encounters. Polymerase chain reaction was used to determine whether DNA markers from the clothing sites were transferred to patients or environmental surfaces. Results: Ninety percent of observed patient encounters included one or more direct or indirect contacts between a physician's white coat and a patient or the environment. Direct contact occurred on average 1.7 times per encounter and indirect contact (i.e., physicians' hands contacting the coat prior to touching the patient or environment) occurred on average 2.3 times per encounter. The figure shows the frequency and distribution of sites of direct and indirect contact with white coats. Of 11 patient encounters with DNA-contaminated white coats, five (45%) resulted in transfer of one or both DNA markers; there were three transfers from sleeve cuffs and three from coat pockets. Conclusion: Contaminated white coats may be an under-appreciated source for transmission of healthcare-associated pathogens. Our results provide support for the bare below the elbows policy, but also highlight the potential for indirect transfer of pathogens from other sites on white coats. Disclosures: All authors: No reported disclosures.